(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
While explicit knowledge can be translated into words, tacit knowledge is informal. In this context, a good articulation between tacit and explicit knowledge can be the key to more effective results in knowledge management. When it comes to the development of clothing products, the articulation of different knowledge must be distributed between sectors, and focused on meeting user needs. In the Product Development Process (PDP), it is in the creation sector that ideas create shapes resulting in the first contact with the models in the collection. Using this perspective, the present research aimed to identify how fashion professionals who work in the clothing PDP manage/apply explicit and tacit knowledge in the creative sector. To achieve this, this research, of a basic nature, with a qualitative approach and an exploratory objective, used interviews with fifteen (15) fashion professionals, working in the clothing PDP. Questions related to the practice of explicit and tacit knowledge were applied. The results showed that, in the clothing PDP creation sector, some activities are guided by explicit knowledge, while others are guided by tacit knowledge, which uses the professional’s experience and repertoire. The results also reflect the importance of knowledge management in the development of clothing products, since explicit and tacit knowledge complement each other during activities, in the quest to achieve common objectives.